2006
DOI: 10.1038/sj.bjc.6603315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socio-economic deprivation on death rates after surgery for upper gastrointestinal tract cancer

Abstract: We hypothesised that socio-economic deprivation in England may be a prognostic factor for death after oesophagectomy or gastrectomy for cancer of the upper gastrointestinal tract. We analysed statistical data from hospital records linked to death records for patients who underwent operations for oesophageal and gastric cancer in England from April 1998 to March 2002. The patients were stratified into quintiles according to the index of multiple deprivation (IMD) (2000) for their place (ward) of residence. Age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
2
20
1
Order By: Relevance
“…Similar results were described in the study of Crumley et al who found that patients older than 65 years had better 3-year survival than younger patients (32% vs. 29%; p=0.017) 42. Some other studies did not find any prognostic significance between different groups of age 4851…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were described in the study of Crumley et al who found that patients older than 65 years had better 3-year survival than younger patients (32% vs. 29%; p=0.017) 42. Some other studies did not find any prognostic significance between different groups of age 4851…”
Section: Discussionsupporting
confidence: 86%
“…Seven dimensions of deprivation are included: income deprivation; employment deprivation; health deprivation and disability; education, skills, and training deprivation; barriers to housing and services; living environment deprivation; and crime. IMD 2004 has been used to examine the association between socioeconomic deprivation and outcomes such as equity of access to care, 23 life expectancy, 24 preterm birth rates, 25 and postsurgical mortality 26 . Full details of the theoretical and practical implementation of the IMD measure, including discussion of its reliability and validity, are available 27…”
Section: Methodsmentioning
confidence: 99%
“…IMD 2004 has been used to examine the association between socioeconomic deprivation and outcomes such as equity of access to care, 23 life expectancy, 24 preterm birth rates, 25 and postsurgical mortality. 26 Full details of the theoretical and practical implementation of the IMD measure, including discussion of its reliability and validity, are available. 27 Using information from the national Census of 2001, the UK Office for National Statistics calculated IMD scores at the Super Output Area (SOA) level.…”
Section: Measures Of Neighborhood Deprivationmentioning
confidence: 99%
“…The survival advantage for these patients is not solely due to differences in cancer stage at presentation or differences in comorbidity between economic groups (3–5). It is also reported that the patients from more affluent areas have a quicker diagnosis, lower operative mortality and a better long term survival (1,2,6).…”
Section: Introductionmentioning
confidence: 99%